Manfaat Senam Dismenorea Bagi Siswi–Siswi Pondok Pesantren Dalam Mengurangi Nyeri Menstruasi Di Pondok Pesantren Imam Asy Syafi’i Genteng Banyuwangi - Miftahul Hakiki; Nurul Eko Widiyastuti (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Community Service Activities carried out will provide knowledge to adolescents about reproductive health. Reproductive health is a series of activities that aim to provide knowledge about reproductive health. According to Notoatmodjo, health counseling activities, it can increase individual knowledge about their health, such as about the advantages and disadvantages. Dysmenorrhea exercise is a physical activity that can be done to reduce stomach cramps during menstruation. From the information obtained from one of the students of the Imam Asy Syafi’i Islamic Boarding School, during menstruation they feel pain so there are some who cannot carry out their activities, such as not being able to go to school, participating in cottage activities and there is one student who has fainted because she feels pain during menstruation. It is hoped that the existence of counseling on reproductive health can lead to positive individual attitudes. A positive attitude is an attitude that can support health. The implementation of this community service was carried out at STIKes Banyuwangi with 123 high school student participants from the Imam Asy Syafi’i Islamic Boarding School and the method used was lectures and questions and answers about the contents of the leaflet, from the number of participants 123 students were divided into 4 groups so that each group consists of 30 female students. The results of this activity are increasing the knowledge of Islamic boarding school students about dysmenorrhea exercises in reducing pain during menstruation.